DIFFERENCE OF THE IMAGE INFORMATION AXIAL PELVIC MRI USING DIFFUSION WEIGHTED IMAGE SEQUENCE WITH THE VARIATION OF B VALUE IN CERVICAL CANCER - Rini Indrati; Distyarini Primadita; Widiana Ferriastuti; Marichatul Jannah; Sri Mulyati; Siti Daryati (Jurnal Riset Kesehatan, 2019)
Cervical cancer is the second most common type of cancer worldwide, it is reaching 15% of all kind of cancer in women. There are several ways to diagnose cervical cancer, one of them is an MRI. One of the MRI sequences which can perform the pathology of cervical cancer is Diffusion-Weighted Image. The aim of this research is to find out the anatomical differences between axial slice image of Pelvic MRI which is using DWI sequence with the variation of b value in the case of cervical cancer, and also to reveal the optimal b value to obtain the image of Pelvic MRI which is using DWI sequence in the case of cervical cancer. The method of this research is experimental with the comparison of static groups. Data is 30 images of axial DWI Pelvic MRI from 10 patients in the case of cervical cancer with 3 different variations of b value, which are 600 s/mm2, 800 s/mm2, and 1000 s/mm2. Assessment of information image data done by the radiologist. Data analysis by Friedman and Wilcoxon Test. The result showed that there are differences of image information between axial Pelvic MRI which is using the DWI sequence with the variation of b value in the case of cervical cancer with a significant p-value less than 0.001. Differences in image information occur in the tumor, expansion of tumor, parametrium until the pelvic wall and lymph. The optimal use of b value for axial Pelvic MRI with DWI sequence in the case of cervical cancer is 600 s/mm2.